2003
DOI: 10.1046/j.1469-8137.2003.00852.x
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical traits of lichens differing in relative desiccation tolerance

Abstract: Summary• Oxidative stress arises when desiccation restricts photosynthesis and light energy is transferred from photo-excited pigments onto ground state oxygen. We tested whether a highly desiccation tolerant lichen, Pseudevernia furfuracea , displays better protection against oxidative stress than more sensitive species, Lobaria pulmonaria and Peltigera polydactyla .• We rehydrated lichens after desiccation periods of 2, 7 and 9 weeks and assessed their viability by measuring CO 2 exchange using IRGA. During … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
56
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(68 citation statements)
references
References 52 publications
3
56
0
1
Order By: Relevance
“…L. pulmonaria, an intermediate desiccation-tolerant lichen, regenerated initial concentrations of GSH only when rehydrated in liquid water, while in P. polydactyla, neither method of rehydration reestablished the initial GSH pool (27). In our system, similar to the case for other lichens (27)(28)(29)(30)(31), ascorbate and glutathione probably contribute significantly to water-soluble antioxidant capacity. The difference between our studies and others and among the others may be explained, as mentioned above, by the choice of species and the variability in the methodologies, particularly in the various pretreatments of the thalli in the laboratory or in performing the rehydration experiments.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…L. pulmonaria, an intermediate desiccation-tolerant lichen, regenerated initial concentrations of GSH only when rehydrated in liquid water, while in P. polydactyla, neither method of rehydration reestablished the initial GSH pool (27). In our system, similar to the case for other lichens (27)(28)(29)(30)(31), ascorbate and glutathione probably contribute significantly to water-soluble antioxidant capacity. The difference between our studies and others and among the others may be explained, as mentioned above, by the choice of species and the variability in the methodologies, particularly in the various pretreatments of the thalli in the laboratory or in performing the rehydration experiments.…”
Section: Discussionsupporting
confidence: 67%
“…There are some studies in which cellular levels of antioxidants were compared in freshly collected lichens and during wetting and drying cycles of lichens normally growing in moist, xeric, and extremely xeric microhabitats (8,9,28,31,43). The glutathione status was shown to vary between species differing in their desiccation tolerance in response to desiccation or rehydration, and the xanthophyll cycle was found to play an antioxidant function during desiccation of lichens (8,9,28,29,31).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, and Heber (2008) report differences in the recovery under different light tretments between mosses collected in autumn-winter or in spring-summer, indicating seasonal acclimation of poikilohydric organisms to the light regime, but they found that in this case it was independent of zeaxanthin accumulation. In lichens the xanthophyll cycle activation cannot either be assumed as a general response to light dissipation under stress conditions because some lichen species, like Pseudevernia furfuracea or the isolated lichen photobiont Trebouxia excentrica, do not increase the xanthophyll DPS upon dehydration or rehydration (Kranner et al, 2003. Relationship between NPQ and desiccation tolerance in lichens has been studied during the last years.…”
Section: Mechanisms Of Light Energy Dissipation In Lichen Algaementioning
confidence: 99%
“…This is made all the more critical by the ability of rock-encrusting lichens and algae to withstand near-complete water losses (Beckett, 1995;Kranner et al, 2003), reducing or eliminating the availability of pre-formed water to the epilithic arthropod fauna during periods of drought. Whether P. lagurus depends primarily on the existing water in food, dew, metabolic water or WVA is unknown.…”
Section: Introductionmentioning
confidence: 99%